The Relationships between Physical Activity, Sleep Duration, Alcohol Consumption, and Hypertension in Adults: Meta-Analysis - Niken Putri Eka Saraspuri; Nisa Nur Kusuma (Journal of Epidemiology and Public Health, 2022)
Background: Hypertension is a disease that causes damage to body systems. Risk factors for hypertension are changes in socioeconomic, environmental, and unhealthy lifestyle such as smoking, lack of physical activity, high-fat and high-calorie foods, and alcohol consumption. This study aims to analyze the relationship between physical activity, sleep duration, and alcohol consumption on the incidence of hypertension in adults with a meta-analysis study. Subjects and Method: This study is a systematic review and meta-analysis with the population: adults (>18 years old). Intervention: low physical activity, short sleep duration and frequent alcohol consumption. Comparison: moderate physical activity, normal sleep duration, and no alcohol consumption. Outcome: the incidence of hypertension. The articles used were obtained from several databases: PubMed, SpringerLink, ScienceDirect, and Google Scholar. The keywords are: “physical activity” OR exercise” AND “sleep duration” AND “alcohol consumption” AND "hypertension" OR “high blood pressure”. The article used was a full-text article with a cross-sectional study design and the results were reported in aOR. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 27 articles in this study came from 4 continents, namely Asia (South Korea, China, Lebanon, Thailand), Africa (Cameroon, Uganda, Ethiopia, Sudan), Europe (Poland, France, Portugal, Spain) and America (United States of America). The forest plot results showed that adults with low physical activity had 1.41 times higher risk to experience hypertension compared to people who did moderate physical activity (aOR = 1.41; 95% CI = 1.22 to 1.62; p < 0.001). Short sleep duration increased the incidence of hypertension by 1.19 times higher compared to normal sleep duration (aOR = 1.19; 95% CI = 1.06 to 1.32; p = 0.002). Frequent alcohol consumption increased the incidence of hypertension by 1.29 times higher compared to no alcohol consumption (aOR=1.29; 95% CI = 1.12 to 1.49; p=0.0006). Conclusion: Physical activity, sleep duration, and alcohol consumption increase the incidence of hypertension in the adult population.